PEMANFAATAN ABU BONGGOL JAGUNG SEBAGAI BAHAN TAMBAH SEMEN PADA PEMBUATAN BATA RINGAN JENIS CLC - Muhammad Aditya Nugraha; Daryati Daryati; Anisah Anisah (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
This study aims to determine the use of corn cob ash as an additive to cement in the production of CLC lightweight bricks according to SNI 03-2156-1991 concerning air flow light brick blocks by autoclaving process. The method used is an experiment in accordance with SNI 03-2156-1991 regarding light brick blocks of air flow with autoclaving process. The test object measures 59 × 19 ×10 cm and uses 45 specimens. The results obtained for dimensional testing exceed the required limits of SNI 03-2156-1991. The compressive strength of lightweight bricks is obtained at variations of 0%, 4%, 6%, 8%, and 10% respectively 3.07 N/mm², 3.68 N/mm², 4.54 N/mm², 4.29 N/mm², and 4 N/mm² with the optimum compressive strength value obtained at 6% variation and non-passing variation at 0% variation with a minimum requirement of 3.6 N/mm². The flexural strength of lightweight bricks is obtained at variations of 0%, 4%, 6%, 8%, and 10% respectively 0.27 N/mm², 0.63 N/mm², 0.81 N/mm², 0.65 N/mm², and 0.76 N/mm with optimum flexural strength values obtained at 6% variation and non-qualifying variations at 0% and 4% variations with a minimum requirement of 0.65 N/mm².